Do Corporate Governance Factors Matter for Financial Distress Prediction of Firms? Evidence from Tiawan. - Wu, Jia-Ling (2007)
A large number of researchers devote themselves to the study of financial distress predictive models over the past decades. The first analysis method, which is Univariate approach, towards predicting model was introduced by Beaver (1966) and Multiple Discriminant Analysis (MDA) was proposed by Altman (1986) thereafter. Due to the fact that these two approaches can not perform precisely to predict a financial distress, Martin (1977) introduces the Logit model applied in the predictive models and Ohlson (1980) even expands selected samples to improve the accuracy rate of prediction. Although prediction models of financial distress have been improved via various applied statistic models, more information should be included to improve the quality of predictive models. Hence, Daily and Dalton (1994a) conduct a study to explore the relationship between corporate governance mechanism and probabilities that companies might experience financial crisis by means of considering both financial and governance variables since corporate governance has been proved that it has a substantial impact on the performance of firms. To investigate whether corporate governance is related to the probability of financial distress, ten governance variables are adopted in this study and the Binary Logit model is employed to establish a financial distress predictive model. The results indicate that seven variables, which are the percentage of shares held by institutional shareholders, the extent of concentration, cash flow rights, the ratio of cash flow to control rights, the ratio of board seats held by outside directors and supervisors, management participation and stock pledge ratio, have a significant impact on the financial distress predictive probability. The classification accuracy rate is also raised by means of adopting governance variables besides financial variables in the predictive models and the predictive model perform differently in the electronic and non-electronic industry. It is also discovered that the qualities of corporate governance in Taiwan still need to be improved. In sum, this study concludes that weak corporate governance leads to higher probability of financial distress.